Pengaruh Media Tangram Magnet terhadap Kemampuan Motorik Halus Siswa Disabilitas Intelektual Ringan - Mufida, Inayatul; Prystiananta, Nostalgianti Citra; Udhiyanasari, Khusna Yulinda (JOEAI (Journal of Education and Instruction), 2025)
This study aims to determine the effect of using magnetic tangrams on the fine motor skills of students with mild intellectual disabilities. The method used was a Single-Subject Research (SSR) design with an A-B design, comparing conditions before (baseline) and after the intervention. The results showed that the use of magnetic tangrams can improve fine motor skills in students with mild intellectual disabilities. This study concludes that magnetic tangrams are an effective learning tool for improving fine motor skills in students with mild intellectual disabilities.   Keywords: Magnetic Tangrams, Fine Motor Skills, Mild Intellectual Disability